Pengaruh Keandalan dan Daya Tanggap Terhadap Kepuasan Pensiunan di PT Taspen (Persero) Kantor Cabang Manado - Julica Esther Sumale; Hongky Dyrgo; Mercy Mantur (Journal of Mandalika Literature, 2025)
The purpose of this research is to look at how the Manado Branch Office of PT TASPEN (Persero) measures up in terms of both responsiveness (X2) and reliability (X1) in relation to customer satisfaction (Y). Using the Slovin formula, a total of 85 respondents were selected for the research sample. We used a questionnaire to gather data, and then we ran the numbers through SPSS's Multiple Linear Regression analysis with a Simultaneous Test (F Test) and a Partial Test (t Test). The study's findings indicate that both responsiveness and reliability, which are independent factors, significantly and positively affect customer satisfaction, the dependent variable. Moreover, Y (Customer Satisfaction) is positively and significantly impacted by the two independent factors. Finally, the Manado Branch Office of PT TASPEN (Persero) affects customer satisfaction through responsiveness and reliability.